Analyzing students’ dropout factors in Open and Distance Learning (ODL) using a DEMATEL method / Mohamad Nafis Ajwad Jusoh - Jusoh, Mohamad Nafis Ajwad (2021)
The outbreak of Covid-19 pandemic has changed many sectors and the lives of people at large. The education becomes one of the affected sectors as all public and private academic institutions need to be closed in preventing the disease from spreading. As an adaptation to this situation, the Open and Distance Learning (ODL) mode of learning is introduced. The ODL helps students to continue the learning process from home, and anywhere as long as they have the devices such as smartphones or laptops, and also the internet connection. However, the report concerning the high dropout rate of massive online open courses (MOOCs) among students has become one of the issues being discussed. As the implementation of MOOCs mode and ODL is almost similar, the issue is now important to be focused. The factors behind the students’ dropout need to be considered. Therefore, identifying the factors that have contributed to the students’ dropout in ODL is very crucial. For that reason, the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method was applied in this study. A DEMATEL method can analyze variable correlations using crisp values and solve complicated systems by providing the cause and effect relationship among components. The DEMATEL method has five steps to be implemented which are constructing the direct relation matrix, normalizing the matrix, calculating the total relation matrix, building up the causal diagram and calculating the weight of factors. Ten sub-factors were selected and classified into four main factors. 50 data were collected from the questionnaire distributed to final semester degree students in UiTM Kuala Terengganu. Based on the analysis on the ten sub-factors, the result obtained presents the academic skill and abilities sub-factors turned out to carry the highest weight value, thus was ranked at the first place. The findings of this study can assist students in recognizing the most influential dropout factors in ODL to plan and make sensible decision for their study.